Saliva Accuracy Analysis as a Non-Invasive Method for Determining Blood Type - Maharani, Dwi Sinta; Firdaus; Desnita, Eka (Denta Journal Kedokteran Gigi, 2026)
Background: A phobia is an excessive, irrational, and persistent fear of something that makes it difficult for someone to carry out certain activities. Psychological disorders, such as a phobia of blood and injections, indicate the need for forensic identification methods that do not require blood samples. Blood type identification plays an important role in forensic cases, especially in matching the blood type of the evidence of victims or perpetrators. Objective: To analyze the accuracy of saliva as a noninvasive method for determining blood type in students of the Faculty of Dentistry, Baiturrahmah University, class of 2021. Method: This was a quantitative observational analytic study with a cross-sectional design. The study population comprised 80 students selected using a simple random sampling technique. Saliva samples were analyzed using the absorption inhibition method and compared with available blood type data. The data were analyzed using SPSS version 23.0, and Fisher's exact test was performed as an alternative to the chi-square test. Results: Blood types A, B, and AB have 100% compatibility in secretor individuals, while blood type O has 0% compatibility because there are no antigens A and B in the saliva. Statistical tests showed a significant level of accuracy between blood type examination through saliva and blood type in the data (p=0.000). Conclusion: Overall, saliva blood type examination has the same level of accuracy as the conventional method.